A prospective multicenter study on varicella-zoster virus infection in children with acute lymphoblastic leukemia - Xiao, Peifang; Cai, Jiaoyang; Gao, Ju; Gao, Wei; Guan, Xianmin; Leung, Alex Wing Kwan; He, Yiying; Zhuang, Yong; Chu, Jinhua; Zhai, Xiaowen; Qi, Benquan; Liu, Aiguo; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background and methods: The study evaluated prognostic factors associated with varicella-zoster virus (VZV) infection and mortality in children with acute lymphoblastic leukemia (ALL) using data from the multicenter Chinese Children’s Cancer Group ALL-2015 trial. Results: In total, 7,640 patients were recruited, and 138 cases of VZV infection were identified. The incidence of VZV infection was higher in patients aged ≥ 10 years (22.5%) or with the E2A/PBX1 fusion gene (11.6%) than in those aged < 10 years (13.25%, P = 0.003) or with other fusion genes (4.9%, P = 0.001). Of the 10 deaths in children with ALL and VZV infection, 4 resulted from VZV complications. The differences between groups in the 5-year overall survival, event-free survival, cumulative recurrence, and death in remission were not statistically significant. The proportion of complex infection was higher in children with a history of exposure to someone with VZV infection (17.9% vs. 3.6%, P = 0.022). Conclusion: VZV exposure was associated with an increased incidence of complex VZV infection and contributed to VZV-associated death in children with ALL.